The Effect of Using PhET in Changing Malaysian Students' Attitude to Learning Physics in a Full Virtual Environment. - Mei Eng Ng; Kah Heng Chua (Pertanika Journal of Social Sciences & Humanities, 2023)
This study investigated the effect of physics inquiry learning using PhET Interactive Simulation on form four students' attitudes toward physics in a fully virtual environment during the COVID-19 pandemic in Malaysia. This quantitative study employed the Quasi-Experimental Design by administering the Attitude Toward Physics Lesson Scale (ATPLS). Fifty-nine form four students from a rural school located in Selangor, Malaysia, participated in this study. The control group (n1= 25) was taught in the standard thematic order as the usual teaching approach by the teacher during online lessons. In eight lessons, students only watched videos related to laboratory experiments that covered Gravitational Force, Newton's Laws, and Gas Laws. Meanwhile, the experimental group (n2= 34) used the PhET Interactive Simulations as a treatment to explore the same topics. All test results underwent a normality test, homogeneity test, and hypothesis evaluation. The data in this study were analyzed using Multivariate Analysis of Covariance (MANCOVA) and Analysis of Covariance (ANCOVA). Findings revealed that PhET Interactive Simulation negatively impacts students' attitudes towards physics inquiry learning during the full virtual online lessons. Further study is expected to pair PhET Interactive Simulation with other e-learning tools or platforms to provide better instant feedback and enhance students' attitudes in physics inquiry learning.